2017
DOI: 10.1002/ejic.201601341
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Catalytic Route for the Synthesis of Silane Coupling Agents Based on the 1,1,3,3‐Tetramethyldisiloxane Core

Abstract: We report herein the study of the selective monofunctionalization of 1,1,3,3-tetramethyldisiloxane (TMDSO) with vinyl-substituted silicon derivatives through the hydrosilylation reaction. An investigation of the use of platinum-and rhodiumbased catalysts in the reactions between TMDSO and exemplary [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In order to avoid hydrosilylation of both dimethylsilyl groups in 1,4-bis(dimethylsilyl)benzene, the equilibrium of the reaction must be shifted toward the formation of monosubstituted products; therefore, for selective monofunctionalization, a slight excess of silane e was required. A similar effect was observed, e.g., for functionalization of 1,1,3,3,-tetramethyldisiloxane with vinylsilanes; 44 however, for functionalization of POSS compounds with 1,4-bis(dimethylsilyl)benzene, a significantly lower excess of silane e had to be used compared with the disiloxanes, which could be explained by the steric properties of the POSS molecules.…”
Section: Resultssupporting
confidence: 63%
“…In order to avoid hydrosilylation of both dimethylsilyl groups in 1,4-bis(dimethylsilyl)benzene, the equilibrium of the reaction must be shifted toward the formation of monosubstituted products; therefore, for selective monofunctionalization, a slight excess of silane e was required. A similar effect was observed, e.g., for functionalization of 1,1,3,3,-tetramethyldisiloxane with vinylsilanes; 44 however, for functionalization of POSS compounds with 1,4-bis(dimethylsilyl)benzene, a significantly lower excess of silane e had to be used compared with the disiloxanes, which could be explained by the steric properties of the POSS molecules.…”
Section: Resultssupporting
confidence: 63%
“…The hydrosilylation occurred in the presence of commercially available chloro(1,5-cyclooctadiene) rhodium(I) dimer ([RhCl(cod)] 2 ). As shown in our previous studies, 20,21,29 the application of this binuclear rhodium catalyst (unlike the commonly used Karstedt's (Pt 2 (dvs) 3 ) or Wilkinson's catalysts) allowed a reduction of 1 over olefins with the retention of excellent selectivity towards b-isomers, and negligible formation of bisadducts if 4-fold excess of 1 was used. Thus, we examined six different allylic derivatives (2a-f) and one vinyl derivative (2g) (Scheme 1).…”
mentioning
confidence: 76%
“…We found that a platinum(0) complex I bearing bulky N-heterocyclic carbene ligand effects hydrosilylation of alkynes with secondary silanes to produce β- E -alkenylsilanes with high yield and excellent stereoselectivity. A broad range of terminal acetylenes and secondary silanes undergo this reaction to afford a lot of symmetrical and unsymmetrical organosilicon compounds which can be used as liquid crystals, 12 solid polymeric electrolytes, 13 coupling agents 14 or monomers for UV induced polymerization. 15 We established the conditions for fully selective synthesis of mono- as well as dialkenylsubstituted β- E -adducts.…”
Section: Discussionmentioning
confidence: 99%